Functional and Oncological Outcomes Following Robot-Assisted and Laparoscopic Radical Prostatectomy for Localized Prostate Cancer With a Large Prostate Volume: A Retrospective Analysis With Minimum 2-Year Follow-Ups - Deng, Wen; Liu, Xiaoqiang; Liu, Weipeng; Zhang, Cheng; Zhou, Xiaochen; Chen, Luyao; Guo, Ju; Wang, Gongxian; Fu, Bin (Frontiers in Oncology, 2021)
Objective We aimed to analyze the perioperative, functional, and oncologic outcomes following robot-assisted radical prostatectomy (RARP) and laparoscopic radical prostatectomy (LRP) for patients with localized prostate cancer (PCa) characterized by a large prostate volume (PV; ≥50 ml) over a minimum of 2 years follow-up. Materials and Methods Patients undergoing RARP and LRP for localized PCa with a large PV were included in the final analysis. The perioperative, functional, and oncologic outcomes were analyzed between the two groups. Results All operations were successfully completed without open conversion in both groups. The mean operative time and estimated blood loss in the RARP group were significantly decreased compared to those in the LRP group (139.4 vs. 159.0 min, p = 0.001, and 124.2 vs. 157.3 ml, p = 0.003, respectively). Patients in the RARP arm had significantly lower proportions of grade II or lower and of higher than grade II postoperative complications compared with those in the LRP group (7.9% vs. 17.1%, p = 0.033, and 1.6% vs. 6.7%, p = 0.047, respectively). No significant differences in terms of the rates of pT3 disease, positive surgical margin, and positive lymph node were noted between the two groups. Moreover, no significant difference in the median specimen Gleason score was observed between the RARP and LRP groups (6 vs. 7, p = 0.984). RARP vs. LRP resulted in higher proportions of urinary continence upon catheter removal (48.4% vs. 33.3%, p = 0.021) and at 3 (65.1% vs. 50.5%, p = 0.025) and 24 (90.5% vs. 81.0%, p = 0.037) months post-operation. The median erectile function scores at 6 and 24 months post-operation in the RARP arm were also significantly higher than those in the LRP arm (15 vs. 15, p = 0.042, and 15 vs. 13, p = 0.026, respectively). Kaplan–Meier analyses indicated that the biochemical recurrence-free survival and accumulative proportion of continence were statistically comparable between the two groups (p = 0.315 and p = 0.020, respectively). Conclusions For surgically managing localized PCa with a large prostate (≥50 ml), RARP had a tendency toward a lower risk of postoperative complications and better functional preservation without cancer control being compromised when compared to LRP.